Anticalculi and antibacterial activity of methanol extract of Holothuria atra - Irwan Irwan; Jefri Saputra Mulia; Softyatuddin Karina; Eli Nurliza (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2024)
Sea cucumbers are a type of marine organism with significant economic worth and potential applications as nutraceuticals. This marine organism possesses possibly useful chemicals, making it a viable alternative for the fisheries product processing businesses. The objective of this study was to assess the efficacy of the methanol extract of Holothuria atra in preventing the formation of calculi and its ability to inhibit the growth of bacteria. Extraction was performed using the maceration method with methanol as the solvent over a period of 72 hours The analysis revealed the presence of four bioactive components in the methanol fraction: alkaloid, triterpenoids, flavonoids, and saponins. In vitro anticalculi activity was assessed by measuring the decomposition of kidney stones (Ca) using an atomic absorption spectrophotometer (AAS). The maximum decline of calcium stones was regarded at a concentration of 500 ppm of sea cucumber extract. The disc diffusion method was employed to assess the antibacterial activity against Escherichia coli and Staphylococcus aureus. The inhibition zone diameter was measured at all concentrations (25%, 50%, 75%, and 100%), indicating their potential as antibacterial agents. The greatest level of antibacterial effectiveness against Escherichia coli was observed at a concentration of 50%, resulting in a zone of inhibition of 1.90 mm. In contrast, the most significant antibacterial activity against Staphylococcus aureus was observed at a concentration of 25%, resulting in a zone of inhibition measuring 4.50 mm.Keywords:Holothuria atraExtractMethanolAnticalculiAntibacteria